Mechanisms of the priming effect of low doses of lipopolysaccharides on leukocyte-dependent platelet aggregation in whole blood - Montrucchio, Giuseppe; Bosco, Ornella; Sorbo, Lorenzo Del; Pecetto, Paolo Fascio; Lupia, Enrico; Goffi, Alberto; Omedè, Paola; Emanuelli, Giorgio; Camussi, Giovanni (Thrombosis and Haemostasis, 2003)
Several studies focused on the ability of bacterial lipopolysaccharides (LPS) in triggering platelet and/or leukocyte activation. The aim of this study was to investigate the molecular mechanisms involved in the aggregation of platelets and in their interaction with leukocytes in whole blood after stimulation with low doses of LPS.LPS did not directly induce platelet aggregation in whole blood, but they primed the aggregation of platelets induced by epinephrine, adenosine diphosphate and arachidonic acid. As shown by cytofluorimetry, platelets neither bind FITC-LPS, nor express the LPS-receptors CD14 and toll-like receptor 4 (TLR4). On the contrary, LPS primed monocytes and to a lesser extent polymorphonuclear neutrophils to adhere to platelets. Both platelet-leukocyte interaction and platelet aggregation in whole blood were inhibited by blockade of CD14 and TLR4. Moreover, the interaction between platelets and leukocytes was inhibited by P-selectin, and by blockade of PAF and reactive oxygen species, suggesting a role of P-selectin and of leukocyte-derived mediators.In conclusion, these results elucidate the mechanisms leading to platelet activation and interaction with leukocytes triggered by LPS. They suggest that the activation of platelets by LPS is mainly dependent on leukocytes and especially monocytes as a result of CD14 and TLR4 engagement. Moreover, we found that leukocyte-platelet interaction was triggered by the synthesis of PAF and the generation of oxygen radicals that induced upregulation of surface expression of P-selectin.
Keywords: Monocytes; platelet-activating factor; radical oxygen; CD14; P-selectin; TLR-4